Incidence and predictive value of social frailty among community-dwelling older adults in Southwest China: A prospective cohort study - Sun, Qian-qian; Tan, Ke; Tang, Hui-yu; Liu, Yan-yan; Zhu, Huan; Qin, Hai; Xia, Xin; Zhang, Min; Chen, Yan-yu; Nie, Shuang-shuang; Wang, Shuang (Frontiers in Public Health, 2023)
Background Few studies have focused on the incidence and correlation of social frailty (SF) with adverse health events in Southwest China. This study aims to explore the predictive value of SF for adverse health events. Methods A 6-year prospective cohort study was employed, a total of 460 community-dwelling older adults aged 65 years and above were analyzed to provide a baseline in 2014. Participants completed two longitudinal follow-ups at 3 (2017, 426 participants involved) and 6 (2020, 359 participants involved) years later. A modified social frailty screening index was used in this study, and adverse health events such as physical frailty (PF) deterioration, disability, hospitalization, falls, and mortality were evaluated. Results Among these participants in 2014, the median age was 71 years, 41.1% were male, and 71.1% were married or cohabiting, up to 112 (24.3%) of them were classified as SF. It was observed that aging (OR = 1.04, 95% CI = 1.00–1.07, P = 0.047) and having family members die in the past year (OR = 2.60, 95% CI = 0.93–7.25, P = 0.068) were risk factors of SF, whereas having a mate (OR = 0.40, 95% CI = 0.25–0.66, P = 0.000) and having family members to help with care (OR = 0.53, 95% CI = 0.26–1.11, P = 0.092) were protective factors of SF. The cross-sectional study demonstrated that SF was only significantly associated with disability (OR = 12.89, 95% CI = 2.67–62.13, P = 0.001) at wave 1. Baseline SF significantly explained the incidence of mortality at the 3-year (medium-term, OR = 4.89, 95% CI = 2.23–10.71, P = 0.000) and 6-year follow-ups (long-term, OR = 2.22, 95% CI = 1.15–4.28, P = 0.017). Conclusion SF prevalence was higher in the Chinese older population. Older adults with SF had a significantly increased incidence of mortality at the longitudinal follow-up. Consecutive comprehensive health management of SF (e.g., avoiding living alone and increasing social engagement) is urgently needed for the purposes of early prevention and multidimensional intervention in adverse health events, including disability and mortality.